Beauty & the briefcase - Morgan, Christopher; Fischoff, Richard; Junger, Gil; Pressly, Jaime 1977-; Coolidge, Jennifer; Dallas, Matt 1982-; Duff, Hilary 1987-; Lux, Danny (ABC Family, 2011)
Lane, a fashion journalist, gets the assignment of a lifetime when Cosmopolitan magazine hires her to write a story about finding love in the workplace. Posing as a corporate assistant, Lane finds herself torn between the office's eligible men in suits and a dashing stranger who sweeps her off her feet. Will she find the 'magic man' who fulfills her fantasy checklist, or will her story have an ending as unexpected as love itself?